Effects of Treatments on Eucalyptus Waste to Produce Cement Composites - Cabral, Matheus Roberto; Nakanishi, Erika Yukari; Santos, Sérgio Francisco [UNESP]; Fiorelli, Juliano (Springer Nature, 2023)
The reuse of waste has been widely used to optimize the performance of cementitious materials. However, several challenges associated with the composition of wood wastes in cement hydration have been pointed out. Therefore, this research investigated the effects of treatments on strand-type particles made from Eucalyptus waste to produce cement composites. Strands measuring 80 mm × 20 mm × 1 mm were produced from Eucalyptus (Eucalyptus spp.) wastes obtained from the pallets industry. Four treatments were studied on the strands, i.e., untreated, cold water, hot water and NaOH. Physical, chemical and microstructural characterizations were performed to assess the effect of these treatments on the strands. The effect of the treatments on the cement hydration was evaluated by assessing the mechanical performance of wood-cement composites. Wettability tests showed that the strands had a surface with a hydrophobic performance except for the strands treated with NaOH. NaOH had the highest values of water absorption after 24 h (186%) while the lowest were those for untreated strands (91%). FTIR showed that the treatments reduced the cellulose and hemicellulose bands. In addition, a reduction in the bands referring to extractives for the treated strands was also identified. For the effects of the treatments on the mechanical properties of the wood-cement composites, it was found that the use of treatments resulted in lower mechanical properties in axial compression. The results for this study showed that the use of treatments does not improve the strand’s physical, chemical and morphological performance and also does not improve the mechanical properties of wood-cement composites. Our findings suggest that producing wood-cement with strands type particles does not require the raw materials treatment.